Fostering Students’ Religious Character Through Arabic Language Teaching and Learning in University - Hasyim, Mohamad Yusuf Ahmad; Santoso, B. Wahyudi Joko; Youssef, Hassan Abdelalim AbdelGawwad; Mudrofin, Mudrofin (Arabi : Journal of Arabic Studies, 2025)
Despite the central role of Arabic in Islamic teachings, its influence on students' religious character in higher education remains underexplored, particularly in Indonesia. Understanding this relationship is essential as Arabic serves as a linguistic tool and a medium for internalizing religious values. This study aims to explore the potential relationship between Arabic language learning and the student's religious character at Universitas Negeri Semarang. Utilizing a case study method, we collected data through interviews, participant observation, and religiosity questionnaires, ensuring data validity through triangulation of methods and sources. The analysis employed thematic analysis to uncover key insights. The findings indicate a positive correlation between Arabic language learning and various dimensions of students' religious character, including ritualistic practices, beliefs, knowledge, and experiential. This finding suggests that Arabic language instruction enhances linguistic skills and plays a crucial role in shaping students' religious identities and values, potentially influencing their attitudes and behaviors in broader contexts.